O solo como material alternativo para o ensino de Ciências e Educação Ambiental: oficina as cores do solo em uma turma do Nono Ano na Escola Hesketh Condurú em Curuçá-PA - BARATA, Rosenilda Neves (2023)
This project was applied with the purpose of demonstrating how it is possible to use natural resources, in this case the soil and/or multicolored clays, for science teaching, approaching a transversal theme, for this the environment. The objective was to reuse the soil/clay as an alternative material to contextualize processes of separation of heterogeneous mixtures and environmental approach with ninth grade students of the Hesketh Condurú School, located in Curuçá, Pará through recycling, reuse and natural paints. The work was carried out through a practical class with the aid of a model in order to talk about the formation of the soil, its horizons, its composition and a guidebook on the soil and the separation of heterogeneous mixtures in the process of manufacturing natural paints, and next, a workshop with natural paints based on soil/clays with an environmental approach through recycling and reuse. The research has a descriptive character with a qualitative approach, which registers and describes the observed facts without interfering with them. It was then observed that the students showed interest in the practical class, thus highlighting for us teachers the importance of changing the way of teaching, allowing students the opportunities to create and relate their day to day with curricular themes, in this way the results will be enriching and satisfactory.